REPRODUCTIVE POTENTIAL OF RIO GRANDE TURKEY HENS IN THE EDWARDS PLATEAU OF TEXASa - John M. Reagan; Kenneth D. Morgan (Wildlife Society Bulletin)
Abstract Between 1973 and 1978, 123 Rio Grande turkey (Meleagris gallopavo intermedia) hens were equipped with radio transmitters. Due to transmitter malfunction, antenna breakage and natural mortality, only 53 of the hens (21 adults and 32 yearlings) were radio‐tracked through the nesting season. Eighteen adults and 10 yearling hens were confirmed nesters. Yearling hens renested at about the same frequency as adults (50% for yearlings and 54% for adults). The average clutch size for all hens was 9.8 eggs. Yearling clutches were slightly larger than adult clutches. Ten of the 53 hens (19%) that were tracked hatched poults. This study indicates that yearling Rio Grande turkey hens will nest, but not as frequently as adults. The percentage of yearlings that produced successful nests was less than l/2 that of adult hens.